1995
DOI: 10.1021/es950462q
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Selected Pesticides and Their Metabolites in Near-Surface Aquifers of the Midwestern United States

Abstract: The occurrence and distribution of selected pesticides and their metabolites were investigated through the collection of 837 water-quality samples from 303 wells across the Midwest. Results of this study showed that five of the six most frequently detected compounds were pesticide metabolites. Thus, it was common for a metabolite to be found more frequently in groundwater than its parent compound. The metabolite alachlor ethanesulfonic acid (alachlor-ESA; 2-[(2,6-diethylphenyl)(methoxymethyl)amino]-2-oxoethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
162
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(172 citation statements)
references
References 39 publications
5
162
0
4
Order By: Relevance
“…Only cyanazine however has such a criteria establishedshaving an unenforceable health advisory level set at 1.0 µg/L. Making the gross assumption that the chlorinated degradates may have similar toxicity as the parent compoundssimilar to what has been found with the The results of this study documented that data on the degradates for cyanazine are critical for understanding its fate and transport in the hydrologic system, similar to what has been found with acetochlor, alachlor, atrazine, and metolachlor (3,4,25,26). Furthermore, the prevalence of the chlorinated degradates of cyanazine found in groundwater suggests that to accurately determine the overall effect of cyanazine on human health and the environment its degradates should also be considered.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Only cyanazine however has such a criteria establishedshaving an unenforceable health advisory level set at 1.0 µg/L. Making the gross assumption that the chlorinated degradates may have similar toxicity as the parent compoundssimilar to what has been found with the The results of this study documented that data on the degradates for cyanazine are critical for understanding its fate and transport in the hydrologic system, similar to what has been found with acetochlor, alachlor, atrazine, and metolachlor (3,4,25,26). Furthermore, the prevalence of the chlorinated degradates of cyanazine found in groundwater suggests that to accurately determine the overall effect of cyanazine on human health and the environment its degradates should also be considered.…”
Section: Resultssupporting
confidence: 61%
“…Indeed, research has documented the presence of CAM and DIA in groundwater (3,4). Little data have been obtained on the environmental occurrence of other cyanazine degradates due to the inherent difficulty in measuring these compounds (15).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, a considerable body of work exists relating to the occurrence of both parent compound pesticides and their metabolites in aquifers (Thurman et al, 1992;Baker et al, 1993;Lawrence et al, 1993;Kolpin et al, 1996;Kolpin et al, 1998;Kolpin et al, 2000a;Kolpin et al, 2000b). In the UK the number of field studies has been limited (Clark et al, 1991;Gooddy et al, 2001;Johnson et al, 2001) with researchers often concentrating on laboratory studies of transport and degradation potential (Johnson et al, 1998;Besien et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research on pesticides has found degradates in surface water (5)(6)(7)(8)(9)(10), groundwater (11)(12)(13), precipitation (14)(15)(16), air (17,18), and sediment (19,20).…”
mentioning
confidence: 99%